FEASIBILITY STUDY OF INDUSTRIAL JAROSITE WASTE AS VITAL MATERIAL FOR CONSTRUCTION: POSITIVE AND NEGATIVE ASPECTS (Malaysian Journal of Civil Engineering, 2018)
Jarosite is a basic hydrous sulphate containing potassium and iron. Jarosite is often produced as a by-product during the purification and refining of zinc. The Jarosite mainly contains iron, sulphur, zinc, calcium, lead, cadmium and aluminium. The work presented here will overview the physical and chemical characteristics of Jarosite and as well as the work done by various authors. This paper will study the potential application of Jarosite in various engineering works such as road construction, airfields, dams, bricks and tiles. The text deals with various positive and negative aspects of using Jarosite for engineering purposes as Jarosite released from industrial process is complex and its quality and quantity make the task more complex for safe disposal. Due to the increasing of annual production of Jarosite, it is a major source of pollution for surrounding environment including soil, vegetation and aquatic life.